1997
DOI: 10.1007/bf00175260
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic states associated with retinal venous occlusion in young adults

Abstract: Background. The etiology of retinal venous occlusion in young patients is not well understood although thrombosis does occur histologically. A search for the risk factors that may lead to thrombosis is highly desirable may contribute to our understanding of the pathogenesis of this complication and may improve our therapeutic strategies. Methods. We studied 17 patients with retinal venous occlusion. All patients were under 45 years of age (mean 37.8 4-7.1). Antiphospholipid antibodies (APAs) and certain hemost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
10
0
1
Order By: Relevance
“…These studies have shown a relatively consistent level of APS frequency in the control population of Ͻ5% but the Eye The two studies by Abu El-Asrar and colleagues (both of which showed a significant increased frequency of LA/ACA) stand out from virtually all other studies in that they also had a extremely high level of all thrombophilic abnormalities detected in their CRVO cohorts. 19,45 A total of 18 abnormalities in their earlier study of 17 patients and 46 abnormalities in 57 patients in their latter study were detected. In the study by Gleuk et al although a very high and significant difference in the incidence of LA was found, there was no difference at all in the incidence of ACA antibodies.…”
Section: Anti-phospholipid Syndromementioning
confidence: 86%
See 1 more Smart Citation
“…These studies have shown a relatively consistent level of APS frequency in the control population of Ͻ5% but the Eye The two studies by Abu El-Asrar and colleagues (both of which showed a significant increased frequency of LA/ACA) stand out from virtually all other studies in that they also had a extremely high level of all thrombophilic abnormalities detected in their CRVO cohorts. 19,45 A total of 18 abnormalities in their earlier study of 17 patients and 46 abnormalities in 57 patients in their latter study were detected. In the study by Gleuk et al although a very high and significant difference in the incidence of LA was found, there was no difference at all in the incidence of ACA antibodies.…”
Section: Anti-phospholipid Syndromementioning
confidence: 86%
“…47 Branch retinal vein occlusion has also been studied with similar findings in terms of the role of APS to those found in the CRVO patients. 45,47 Thus in conclusion APS may play a role in CRVO but very disparate results have been obtained due to many studies probably lacking adequate statistical power.…”
Section: Anti-phospholipid Syndromementioning
confidence: 99%
“…Homocysteine level was significantly increased in patients with iCRVO when compared with that in non-iCRVO patients and control subjects (166) . Other reported potential associations include deficiencies of the coagulation inhibitor proteins C and S and antithrombin III, whereas the role of reduced levels of Factor XII remains controversial with some studies suggesting an association while others do not (8,23,160,278) .…”
Section: A Etiologymentioning
confidence: 99%
“…In a multivariate analysis though there was no additive effect of elevated fibrinogen levels to the risk of RVO [28]. While several case-control studies did not find any significant differences between fibrinogen levels of RVO patients and controls [11,29,30,31,32], some smaller studies discovered significant differences [3,33,34,35]. High fibrinogen levels may create hypercoagulable states by increasing blood viscosity, red blood cell aggregation, velocity of platelet aggregation and platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%